Understanding the factors underlying partnership working: A case study of Northumberland National Park, England. (January 2016) - Austin, Richard; Thompson, Nicola; Garrod, Guy
Highlights: This article reports the results of a research project on partnership working in Northumberland National Park. It was found that a range of governance factors, with a relatively high degree of control, and a range of behavioural factors, with a relatively low degree of control, contribute to the performance of any given partnership. In conclusion, an awareness of these factors from the outset may increase the chances of a successful approach to working in partnership. Abstract: Although rural partnership working is a well-researched area, less attention has been paid to the particular challenges in IUCN Category V protected areas. This paper explores the policy and practice of partnership working in a case study Category V area—Northumberland National Park, England. Qualitative research was conducted through documentary analysis and semi-structured interviews with a sample of 23 stakeholders involved in the management of this protected area. It was found that a convoluted institutional history has shaped the present day approach to its management. The processes driving partnership working were understood in terms of governance factors with a relatively high degree of control and behavioural factors with a relatively low degree of control. There was a tacit acceptance among actors that success was dependent upon uncontrollable factors and in particular inter-personal relations between representatives of stakeholder bodies. These findings are important for all IUCN Category V protected areas reliant upon working within stakeholder partnerships to achieve sustainable development objectives. Management bodies can benefit from examining the history of these often complex webs of relationships and the implications for communications between organisations if they are to understand the processes that underpin this form of governance.